2009
DOI: 10.1289/ehp.11771
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Exposure to Polychlorinated Biphenyls Interferes with Experience-Dependent Dendritic Plasticity and Ryanodine Receptor Expression in Weanling Rats

Abstract: BackgroundNeurodevelopmental disorders are associated with altered patterns of neuronal connectivity. A critical determinant of neuronal connectivity is the dendritic morphology of individual neurons, which is shaped by experience. The identification of environmental exposures that interfere with dendritic growth and plasticity may, therefore, provide insight into environmental risk factors for neurodevelopmental disorders.ObjectiveWe tested the hypothesis that polychlorinated biphenyls (PCBs) alter dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
214
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(237 citation statements)
references
References 84 publications
(124 reference statements)
22
214
1
Order By: Relevance
“…The difference in potency, as compared with the pM-nM range reported here, may be due to drastic differences in assay conditions. Specifically, (Wayman et al, 2012b;Yang et al, 2009) supporting the pM to nM toxicity range demonstrated in the current study.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The difference in potency, as compared with the pM-nM range reported here, may be due to drastic differences in assay conditions. Specifically, (Wayman et al, 2012b;Yang et al, 2009) supporting the pM to nM toxicity range demonstrated in the current study.…”
Section: Discussionsupporting
confidence: 77%
“…Organisms exposed during development to PCB 95 and Aroclor 1254, a mixture with increased ortho-substituted PCBs, have altered dendritic arborization in the hippocampus (Yang et al, 2009) and altered RyR1 and RyR, isoform 2 (RyR2) expression in their cerebellum. In these studies, the exposed animals had altered learning and had PCB congeners in their brains that consisted of numerous RyR active congeners including PCB 99, 153, 170, 180, 183, and 187 but did not contain PCB 77, 126, and 169 (Yang et al, 2009). Another study with weanling mice exposed to a mixture of PCB 28, 52, 101, 138, 153, and 180 through lactation displayed age specific disruption in motor function and persistent anxiety like behavior (Elnar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since NO participates in synaptic plasticity, neurite outgrowth and extension, synaptogenesis, neuronal proliferation and maturation (Holscher, 1997;Sanchez-Islas and Leon-Olea, 2004;Wu et al, 1994), the early PCB-induced changes in NOS activity may be associated with altered nervous system development and function (Kodavanti, 2005). Others have suggested that PCB-induced disruption of thyroid hormone signaling in PCB-exposed animals may explain the long-term effects of developmental PCB exposure on nervous system structure and function (Yang et al, 2009). Indeed, perinatal exposure to PCB significantly lowers circulating thyroid hormone levels in rodents Zoeller and Crofton, 2000) and maternal exposure to PCBs is associated with an elevation in thyroid and thyroglobulin antibodies that can pass through the placenta and interfere with thyroid status in the fetus (Langer et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some PCB (and OH-PCB) congeners are estrogenic (Matthews et al, 2007;Wang et al, 2006). Some PCB congeners bind to the ryanodine receptor with high affinity and can alter calcium signaling in cells of the central nervous system (Pessah et al, 2009;Yang et al, 2009). Our Relationship 3, modeling the effect of PCBs on IQ, cannot separate out these mechanisms.…”
Section: Meta-analysismentioning
confidence: 99%